2017
DOI: 10.3892/mmr.2017.7912
|View full text |Cite
|
Sign up to set email alerts
|

PTEN promotes apoptosis of H2O2‑injured rat nasal epithelial cells through PI3K/Akt and other pathways

Abstract: Chronic rhinosinusitis (CRS) is a form of chronic inflammation of the nasal cavity and paranasal sinus with multi‑causal pathogenesis, including oxidative stress. Several lines of evidence have demonstrated that the phosphatase and tensin homolog gene (PTEN) can inhibit the activation of phosphoinositide 3‑kinase (PI3K) to affect phosphorylation of Akt. Importantly, the PI3K/PTEN/Akt signaling pathway is associated with various types of tumors, chronic inflammatory diseases, and autoimmune disease through its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Caspase-3 is widely recognized as a pro-apoptosis factor [22]. Meanwhile, AKT signaling pathway is closely associated with cell growth [23,24]. In the current study, we found the protein content of cleaved caspase-3 was upregulated in miR-338-5p mimic transfected cells.…”
Section: Mir-338-5p Overexpression Suppressed the Growth And Invasionsupporting
confidence: 48%
“…Caspase-3 is widely recognized as a pro-apoptosis factor [22]. Meanwhile, AKT signaling pathway is closely associated with cell growth [23,24]. In the current study, we found the protein content of cleaved caspase-3 was upregulated in miR-338-5p mimic transfected cells.…”
Section: Mir-338-5p Overexpression Suppressed the Growth And Invasionsupporting
confidence: 48%
“…Previous report has demonstrated that PTEN accelerates cell apoptosis via PI3/AKT pathway [28]. Moreover, TRIM27 has enhanced the phosphorylation of AKT pathway in colorectal cancer [5].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this knowledge, it is important to investigate whether mitophagy is involved in inflammatory injury in nasal epithelial cells. In addition to mitophagy, phosphatase and tensin homolog (PTEN) is the intrinsic defender of nasal and sinus inflammatory injury (25,26). PTEN functions as a tumor suppressor involving in the regulation of the cell growth and differentiation (27).…”
Section: Pten Enhances Nasal Epithelial Cell Resistance To Tnfα-inducmentioning
confidence: 99%